2023
DOI: 10.1177/13506501231167621
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aviation anti-wear additives on tribofilm formation and micropitting propensity

Abstract: This article studies the effect of anti-wear additives on micropitting and tribofilm formation. In particular, anti-wear additives used in aviation applications have been compared against a commonly used automotive anti-wear additive (zinc dialkyldithiophosphate ((ZDDP)) that is known to promote micropitting. All tests were performed under test conditions representative of the Power GearBox within Rolls-Royce's new engine, the UltraFan©. Tests using a micropitting rig found that ZDDP formed micropits the faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…69 The thermostat was sufficiently efficient to ensure that the average system temperature was within 10 K of the target value at the chosen sliding velocity. The selected range of temperatures and pressures spans those expected in applications of TCP such as antiwear additives in gearboxes for gas turbine engines 26 and as vapour-phase lubricants. 58…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…69 The thermostat was sufficiently efficient to ensure that the average system temperature was within 10 K of the target value at the chosen sliding velocity. The selected range of temperatures and pressures spans those expected in applications of TCP such as antiwear additives in gearboxes for gas turbine engines 26 and as vapour-phase lubricants. 58…”
Section: Methodsmentioning
confidence: 99%
“…At high temperatures, TCP molecules form relatively thick (60–100 nm) thermal films on steel surfaces; 34 however, it forms thinner tribofilms (∼20 nm) on rubbing surfaces. 26 This is much thinner that the ZDDP tribofilms that form on rubbing steel surfaces (∼100 nm). 26…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Godfrey found that TCP molecules formed a layer of iron phosphate film on the iron surface. Saba et al. , also found that TCP molecules reacted on Fe-based surfaces to form nodular films of iron polyphosphate rather than iron phosphide, as some thought. , Moreover, experiments have shown that TCP molecules form thicker thermal films but thinner tribofilms on steel surfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…30,31 Moreover, experiments have shown that TCP molecules form thicker thermal films but thinner tribofilms on steel surfaces. 32,33 Although there have been some studies on TCP and TNBP antiwear additives, these studies have not provided a systematic elucidation and comparison of the tribochemical reactions and tribological properties of the two additives. The influence of the oxygen content of the surface on these two antiwear additives has also not been systematically addressed, especially at the atomic scale.…”
Section: ■ Introductionmentioning
confidence: 99%